Stories of self, us, and now: narrative and power for health equity in grassroots community organizing - Haapanen, Krista A.; Christens, Brian D.; Freeman, Hannah E.; Speer, Paul W.; Crowell-Williamson, Gavin A. (Frontiers in Public Health, 2023)
Introduction Community organizing initiatives, which build power through cycles of listening, participatory research, collective action, and reflection, have demonstrated the capacity to intervene on, complicate, and resist dominant societal narratives while promoting alternative public narratives focused on shared values and hope for a better future. Methods To explore processes of public narrative change and their relationship to community and organizational empowerment, we interviewed 35 key leaders in community organizing initiatives in Detroit, MI and Cincinnati, OH about how narrative change takes place within community organizing practices. Results Leaders’ perspectives revealed crucial roles for narrative and storytelling in guiding individual and collective behavior, supporting the development of relationships of trust and accountability, and linking personal and collective experiences to pressing social issues. Discussion Findings from this study indicate that systemic change is a labor-intensive process and one that requires the development of leaders (stories of self) and the cultivation of collective structures (stories of us) capable of enacting power to effect change with urgency (stories of now). We conclude by discussing implications of these findings for public narrative interventions and related health equity promotion efforts.